Amplification of vibration induced nystagmus in patients with peripheral vestibular loss by head tilt - Shemesh, Ari Aharon; Kattah, Jorge C.; Zee, David S.; Zuma E Maia, Francisco; Otero-Millan, Jorge (Frontiers in Neurology, 2024)
Introduction In patients with unilateral loss of vestibular function (UVL) vibration of the skull leads to a response of the vestibulo-ocular reflex (VOR) called vibration-induced nystagmus (VIN), with slow phases usually directed toward the paretic ear. This response is thought to result from the difference between the neural discharge in semicircular canal afferents from the healthy and the affected labyrinth. The brain interprets this difference as a sustained imbalance in angular (rotational) vestibular tone, which in natural circumstances would only occur when the head was rotating at a constant acceleration. Methods To study this effect, we used a contemporary model of the neural network that combines sensory information about head rotation, translation, and tilt relative to gravity to estimate head orientation and motion. Based on the model we hypothesize that in patients with UVL, the brain may estimate not only a “virtual” rotation from the induced canal imbalance but also a subsequent “virtual” translation from the incorrect computation of the orientation of the head relative to gravity. If this is the case, the pattern of vibration-induced nystagmus will depend on the orientation of the head relative to gravity during the stimulation. This model predicts that this “virtual” translation will alter the baseline VIN elicited with the head upright; augmenting it when the affected ear is down and diminishing it when the affected ear is up. Results Confirming this hypothesis, we recorded VIN in 3 patients with UVL (due to vestibular neuritis) in upright, right ear-down, and left ear-down positions and each showed the expected pattern. Discussion From a practical, clinical view, our results and modeling suggest that positional VIN might reveal a hidden imbalance in angular vestibular tone in patients with UVL, when patients have equivocal signs of a vestibular imbalance, such as a minute amount of spontaneous or vibration-induced nystagmus with the head upright. This research provides insights into the underlying mechanisms of vestibular processing, the analysis of nystagmus in patients with UVL, and guides the design of a new bedside diagnostic test to assess vestibular function in patients with dizziness and imbalance.